THE APPLICATION OF THE EULER-LAGRANGE EQUATION SOLUTION TO THE PROBLEM OF THE DYNAMICS OF THE SYSTEM "BRIDGE-TRAIN" - Raspopov, O. S.; Rusu, S. P.; Artemov, V. Ye. (Science and Transport Progress, 2007)
The questions of application of the Euler-Lagrange equations to the decision of forced vibration problem of system «bridge–train» are considered. The account of dynamic features of moving loading and bridge span beams are made.